A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets
By encapsulating metal foil and participating in protective heat treatment, the problems of coercive force and oxygen content of neodymium iron boron magnets are solved, performance improvement and process simplification are achieved, and are suitable for traditional processes.
Patent Information
- Application Number
- CN202011204244.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-11-02
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-11-02
AI Technical Summary
In the sintering preparation, the intrinsic coercive force is difficult to improve due to crystal defects and oxidation deformation, and the existing anti-oxidation measures are costly or cumbersome.
Encapsulated with metal foil and participated in protective heat treatment, improving the crystal structure and reducing oxygen content through melt infiltration, simplifying the process flow.
The intrinsic coercive force of neodymium iron boron magnets is improved, the oxygen content is reduced, and the production efficiency is significantly improved, and the process flow is simplified.
Smart Images

Figure BDA0002756485140000051 
Figure BDA0002756485140000061 
Figure BDA0002756485140000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnetic materials, and in particular to a sintering preparation method for improving the intrinsic coercive force of a neodymium iron boron magnet. Background Art
[0002] Sintered magnets, especially sintered NdFeB permanent magnet materials, as the third-generation rare earth permanent magnet materials with the largest magnetic energy product and the most advanced, play a vital role in the development of modern industrial technology, especially in the application of disk drives, air-conditioning compressors, motors, etc., and have even more important practical significance for the sustainable development strategy of developing clean and renewable energy.
[0003] Intrinsic coercivity is an important indicator to measure the anti-demagnetization ability of magnets. It indicates the coercivity when the magnetization intensity in the magnet degenerates to zero. In the use of magnets, the higher the coercivity of the magnet, the better the temperature stability. However, in the sintering preparation of NdFeB magnets, the increase of intrinsic coercivity is limited due to crystal defects.
[0004] At the same time, in the process of manufacturing sintered NdFeB permanent magnet materials, oxygen will inevitably enter the magnet from the atmosphere. Generally speaking, the oxidation is most serious in the powder making, magnetic field orientation and pressing stages. If the oxygen that enters cannot be discharged before sintering and heating, it will cause oxidation deformation of the magnet, seriously affecting the comprehensive performance of the magnet such as magnetic properties, and causing the magnet to be scrapped.
[0005] In order to control the content of oxygen in the magnet, the industry adopts a variety of anti-oxidation measures in each process of preparing NdFeB magnets. For example, CN103184051A disclosed by the Chinese Patent Office, an anti-oxidant for preparing sintered NdFeB permanent magnet materials, designs an anti-oxidant added to NdFeB powder, thereby improving the particle fluidity of NdFeB powder, blocking the contact between air and powder particles, and increasing the hydrophobicity of particles, achieving the anti-oxidation and moisture-proof requirements of NdFeB powder, so that the NdFeB pressed green body can be exposed to the atmosphere. In addition, the Chinese Patent Office also disclosed CN108511180A, a method for preparing an anti-oxidation NdFeB magnet, which adopts the method of introducing argon gas after vacuuming the sintering furnace and then turning on the fan in the sintering furnace to wash the furnace, which will discharge the oxygen and water vapor adsorbed in the sintering furnace, prevent the reaction of rare earth and oxygen in the NdFeB magnet green body, and avoid oxidation deformation during magnet sintering shrinkage.
[0006] However, the above methods may be costly or complicated. Summary of the invention
[0007] In order to solve the problem that the lattice defects of NdFeB magnets caused by the sintering preparation process and the like limit the improvement of the intrinsic coercivity in the existing industrial production of sintered NdFeB magnets, the present invention provides a sintering preparation method for improving the intrinsic coercivity of NdFeB magnets.
[0008] The objects of the present invention are:
[0009] 1. Improve the intrinsic coercivity of NdFeB magnets;
[0010] 2. Reduce the oxygen content of NdFeB magnets;
[0011] 3. Improve the production efficiency of low-oxygen NdFeB magnets;
[0012] To achieve the above objectives, the present invention adopts the following technical solutions.
[0013] A sintering preparation method for improving the intrinsic coercivity of a NdFeB magnet, the sintering preparation method comprising:
[0014] The magnet is oriented and molded into powder, then wrapped with metal foil and vacuum-formed, and then subjected to protective heat treatment to obtain a neodymium iron boron magnet.
[0015] In the technical solution of the present invention, the key point is the sintering process of protective heat treatment after metal foil wrapping, and the melting and infiltration of metal foil are used to achieve alloy diffusion, improve the internal crystal structure of the magnet, modify the grain boundary, increase the densification of the magnet, and enhance the intrinsic coercive force and other properties of the magnet. At the same time, the oxygen-isolated sintering under the metal foil wrapping reduces the oxygen content in the magnet, and due to the omitted metal foil peeling process, compared with other existing technologies, the technical solution of the present invention is obviously greatly improved in simplicity and feasibility of the solution, and can be well applied to traditional processes.
[0016] As a preferred embodiment of the method of the present invention, the magnet powder is obtained by melting, rapidly solidifying, hydrogen breaking and powdering the primary magnet product R-Fe-BM.
[0017] After the conventional pretreatment described above, the magnet is first formed into powder, which is convenient for subsequent molding and sintering operations.
[0018] As a preferred embodiment of the method of the present invention,
[0019] R is at least one of Nd, Pr, Tb, Dy, Gd, La, Ho and Ce;
[0020] The M is at least one of Al, Ga, Cu, Zr and Co.
[0021] The above components are all components of common NdFeB magnets, and the technical solution of the present invention has good universality for the smelting and sintering of common magnets.
[0022] As a preferred embodiment of the method of the present invention, the mass content of R in the primary magnet is 26-35wt%, the mass content of B is 0.8-1.2wt%, the mass content of M is 0.1-5.0wt%, and the balance is Fe.
[0023] The final sintering preparation effect of the magnet preliminary product with the above ratio is better.
[0024] As a preferred embodiment of the method of the present invention, the particle size of the magnet powder is 2 to 5 μm.
[0025] The magnet powders within the above particle size range have better sintering preparation effects. Generally, the smaller the particle size of the powder, the more fluid the powder will be. However, if the particle size is too small, the powder will easily agglomerate and form agglomerates. If the agglomerates are not removed in time, the sintering preparation after pressing will be greatly adversely affected. If the particle size of the powder is too large, the pressing and subsequent sintering preparation effects will also be reduced.
[0026] As a preferred embodiment of the method of the present invention,
[0027] The metal foil composition includes at least one low melting point metal;
[0028] The low melting point metal includes at least one of Al, Ga, Mg, Cu and Sn.
[0029] Metal foil needs to achieve the effect of inward diffusion to optimize the crystal structure during the sintering preparation process. Therefore, low-melting-point metals are selected as the main components of metal foil. The content of low-melting-point metals in metal foil is 0.01-99.9wt%, which can effectively reduce the diffusion difficulty and improve the diffusion effect, and achieve good effects such as repairing grain boundaries, promoting liquid phase sintering, and densification of magnets. At the same time, low-melting-point metals can further save the process of unpacking packaging paper and improve production efficiency. However, in addition to the above-mentioned low-melting-point metals, any metal that can achieve the effect of optimizing grain boundaries can be used as the main component or added component of metal foil.
[0030] As a preferred embodiment of the method of the present invention, the metal foil contains Al and / or Sn.
[0031] On the basis of the above-mentioned low melting point metals, Al and / or Sn are further selected as the main components of the metal foil, and the content of Al and / or Sn in the metal foil is 0.01-99.9wt%. This is mainly because Al and / or Sn can further produce strong reducing properties under the high temperature conditions of sintering preparation, "extracting" the oxygen in the matrix components, and forming a dense anti-oxidation film to further prevent the oxidation of the magnet, so that the NdFeB magnet not only has the characteristics of low oxygen content, but also has a certain anti-oxidation ability.
[0032] Preferably, the thickness of the metal foil is 0.001-0.200 mm.
[0033] The metal foil can ensure a smooth appearance and a high degree of adhesion to the powder during pressing and molding after encapsulation, and can further ensure a better pressing and molding effect.
[0034] Preferably, the metal foil has a thickness of 0.001 to 0.02 mm.
[0035] The use of metal foil with the above thickness has better effect.
[0036] As a preferred embodiment of the method of the present invention, the vacuum shaping comprises the following steps: placing the magnet powder wrapped by metal foil into a vacuum bag, and then sequentially performing vacuuming, isostatic pressing and removing the vacuum bag to balance the pressure.
[0037] Vacuum molding refers to pressing and molding under vacuum conditions. Vacuum pressing and molding can further prevent the oxygen content of the magnet from increasing during the pressing and molding process, and is conducive to pressing and molding to obtain a preset shape.
[0038] As a preferred embodiment of the method of the present invention,
[0039] The protective heat treatment is carried out in a vacuum or protective atmosphere;
[0040] The protective heat treatment includes sintering treatment, tempering treatment and aging treatment.
[0041] Protective heat treatment in vacuum or protective atmosphere can further prevent the oxygen content of the magnet from increasing, ensuring better sintering preparation results.
[0042] As a preferred embodiment of the method of the present invention,
[0043] The sintering treatment temperature is 1030-1100° C., and the treatment time is 1-10 hours;
[0044] The tempering treatment temperature is 850-950°C and the treatment time is 1-10 hours;
[0045] The aging treatment temperature is 450-650° C., and the treatment time is 1-10 hours.
[0046] The heat treatment effects under the above conditions are better.
[0047] The beneficial effects of the present invention are as follows:
[0048] First, the present invention uses metal foil to wrap and isostatically compact, and the metal foil is involved in the sintering heat treatment process of the NdFeB magnet. The diffusion of the components in the metal foil optimizes the grain boundaries of the magnet, repairs the grain boundaries, improves the crystal structure, and thus improves the intrinsic coercive force of the magnet;
[0049] 2. In the preparation method of the present invention, the metal foil is closely attached to the NdFeB green body and participates in the sintering process, protecting the NdFeB green body from oxidation and reducing the oxygen content in the NdFeB magnet;
[0050] Third, in the preparation method of the present invention, the metal foil and the NdFeB green body are closely attached to each other and participate in the sintering process, which saves the process of removing the packaging paper and improves the production efficiency. DETAILED DESCRIPTION
[0051] The specific implementation modes of the present invention are further described below.
[0052] Unless otherwise specified, the raw materials used in the present invention can be purchased from the market or are commonly used in the art. Unless otherwise specified, the methods in the following embodiments are all conventional methods in the art.
[0053] The technical solution of the present invention is further described below in conjunction with specific implementation methods.
[0054] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0056] Example 1
[0057] A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets comprises the following steps:
[0058] Nd 28.7 -Dy 2.5 -Al 0.15 -Cu 0.12 -Co 1.5 -Ga 0.31 -Zr 0.1 -B 0.96 -Fe 余 The materials were smelted to form flakes with a thickness of 0.3 mm. The obtained alloy flakes had clear phase boundaries. They were then mechanically crushed, hydrogen-broken, and jet-milled to a Sauter mean diameter (SMD) of 3.4 μm to obtain magnet powder. The magnet powder was placed in a 15 kOe magnetic field for orientation molding to obtain a green body with a green body density of 3.95 g / cm 3The green body was then placed in a glove box with an oxygen content of less than 0.05 vol% and wrapped with 0.02 mm thick aluminum foil, in which the Al content was 99 wt%. The wrapped green body was placed in a vacuum bag and evacuated, and isostatically pressed at a pressure of 220 MPa to obtain a density of 4.65 g / cm 3 The NdFeB intermediate is placed in a sintering furnace for vacuum sintering, first sintered at 1065°C for 330 minutes, then tempered at 900°C for 150 minutes, and finally aged at 490°C for 240 minutes to obtain a NdFeB magnet.
[0059] Comparative Example 1
[0060] The specific operation is the same as that of Example 1, except that a polyethylene film of equal thickness is used to replace the aluminum foil for wrapping, vacuuming, and isostatic pressing to form a NdFeB intermediate, and the polyethylene film is removed before sintering.
[0061] Test 1
[0062] The NdFeB magnets prepared in Example 1 and Comparative Example 1 were tested and compared. The test and comparison results are shown in Table 1.
[0063] Table 1: Detection and comparison results.
[0064]
[0065] It can be clearly seen from Table 1 above that after being processed by the technical solution of the present invention, the density and remanence properties of the NdFeB magnet are improved, the intrinsic coercivity is increased by 1.63kOe, the oxygen content is reduced by 172ppm, and the Al content in the composition is increased by 0.06wt%. That is, only the difference in whether there is encapsulation during sintering has produced a relatively obvious performance difference. The technical solution of the present invention optimizes the performance of the magnet in an extremely simple way.
[0066] Example 2
[0067] A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets comprises the following steps:
[0068] Nd 28.7 -Dy 2.5 -Al 0.15 -Cu 0.12 -Co 1.5 -Ga 0.31 -Zr 0.1 -B 0.96 -Fe 余The materials were smelted to form flakes with a thickness of 0.2 mm. The obtained alloy flakes had clear phase boundaries. They were then mechanically crushed, hydrogen-broken, and jet-milled to an average diameter (SMD) of 3.4 μm to obtain magnet powder. The magnet powder was placed in a 15 kOe magnetic field for orientation molding to obtain a green body with a green body density of 3.95 g / cm 3 The green body was then placed in a glove box with an oxygen content of less than 0.05 vol% and wrapped with aluminum foil with a thickness of 0.04 mm. The Al content in the metal foil was 99 wt%. The wrapped green body was placed in a vacuum bag and evacuated. After isostatic pressing at a pressure of 220 MPa, a density of 4.65 g / cm was obtained. 3 The NdFeB intermediate is placed in a sintering furnace for vacuum sintering, first sintered at 1065°C for 330 minutes, then tempered at 900°C for 150 minutes, and finally aged at 490°C for 240 minutes to obtain a NdFeB magnet.
[0069] Comparative Example 2
[0070] The specific operation is the same as that of Example 2, except that a polyethylene film of equal thickness is used to replace the aluminum foil for wrapping, vacuuming, and isostatic pressing to form a NdFeB intermediate, and the polyethylene film is removed before sintering.
[0071] Test 2
[0072] The NdFeB magnets prepared in Example 2 and Comparative Example 2 were tested and compared. The test and comparison results are shown in Table 2.
[0073] Table 2: Detection and comparison results.
[0074]
[0075] It can be clearly seen from Table 2 above that after being processed by the technical solution of the present invention, the density and remanence properties of the NdFeB magnet are improved, and the intrinsic coercivity is increased by 1.04kOe, the oxygen content is reduced by 136ppm, and the Al content in the composition is increased by 0.04wt%. That is, only the difference in whether there is encapsulation during sintering has produced a relatively obvious performance difference. The technical solution of the present invention optimizes the performance of the magnet in an extremely simple way.
[0076] Example 3
[0077] A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets comprises the following steps:
[0078] Nd 28.7 -Dy 2.5 -Al 0.15 -Cu 0.12 -Co 1.5 -Ga 0.31-Zr 0.1 -B 0.96 -Fe 余 The materials were smelted to form flakes with a thickness of 0.2 mm. The obtained alloy flakes had clear phase boundaries. They were then mechanically crushed, hydrogen-broken, and jet-milled to an average diameter (SMD) of 3.4 μm to obtain magnet powder. The magnet powder was placed in a 15 kOe magnetic field for orientation molding to obtain a green body with a green body density of 3.95 g / cm 3 The green body was then placed in a glove box with an oxygen content of less than 0.05 vol% and wrapped with 0.02 mm thick tin foil, the Sn content in the tin foil was 99 wt%, and the wrapped green body was placed in a vacuum bag and evacuated, and isostatically pressed at a pressure of 220 MPa to obtain a density of 4.65 g / cm 3 The NdFeB intermediate is placed in a sintering furnace for vacuum sintering, first sintered at 1065°C for 330 minutes, then tempered at 900°C for 150 minutes, and finally aged at 490°C for 240 minutes to obtain a NdFeB magnet.
[0079] Comparative Example 3
[0080] The specific operation is the same as that of Example 3, except that a polyethylene film of equal thickness is used instead of tin foil for wrapping, vacuuming, and isostatic pressing to form a NdFeB intermediate, and the polyethylene film is removed before sintering.
[0081] Test 3
[0082] The NdFeB magnets prepared in Example 3 and Comparative Example 3 were tested and compared. The test and comparison results are shown in Table 3.
[0083] Table 3: Detection and comparison results.
[0084]
[0085] It can be clearly seen from Table 3 above that after being processed by the technical solution of the present invention, the density and remanence properties of the NdFeB magnet are improved, the intrinsic coercivity is increased by 0.83kOe, the oxygen content is reduced by 184ppm, and the Sn content in the composition is increased by 0.07wt%. That is, only the difference in whether there is encapsulation during sintering has produced a relatively obvious performance difference. The technical solution of the present invention optimizes the performance of the magnet in an extremely simple way.
[0086] Example 4
[0087] A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets comprises the following steps:
[0088] Nd 23.0 -Pr 5.4 -Dy 2.5-Al 0.15 -Cu 0.12 -Co 1.5 -Ga 0.31 -Zr 0.1 -B 0.96 -Fe 余 The materials were smelted to form flakes with a thickness of 0.2 mm. The obtained alloy flakes had clear phase boundaries. They were then mechanically crushed, hydrogen-broken, and jet-milled to an average diameter (SMD) of 3.4 μm to obtain magnet powder. The magnet powder was placed in a 15 kOe magnetic field for orientation molding to obtain a green body with a green body density of 3.95 g / cm 3 The green body was then placed in a glove box with an oxygen content of less than 0.05 vol% and wrapped with 0.02 mm thick aluminum foil, in which the Al content was 99 wt%. The wrapped green body was placed in a vacuum bag and evacuated, and isostatically pressed at a pressure of 220 MPa to obtain a density of 4.65 g / cm 3 The NdFeB intermediate is placed in a sintering furnace for vacuum sintering, first sintered at 1065°C for 330 minutes, then tempered at 900°C for 150 minutes, and finally aged at 490°C for 240 minutes to obtain a NdFeB magnet.
[0089] Comparative Example 4
[0090] The specific operation is the same as that of Example 4, except that a polyethylene film of equal thickness is used to replace the aluminum foil for wrapping, vacuuming, and isostatic pressing to form a NdFeB intermediate, and the polyethylene film is removed before sintering.
[0091] The NdFeB magnets prepared in Example 4 and Comparative Example 4 were tested and compared. The test and comparison results are shown in Table 4.
[0092] Table 4: Detection and comparison results.
[0093]
[0094]
[0095] After being processed by the technical solution of the present invention, the density and residual magnetic properties of the NdFeB magnet are improved, the intrinsic coercive force Hcj is improved, and the oxygen content is reduced.
[0096] It can be clearly seen from Table 4 that after being processed by the technical solution of the present invention, the density and remanence properties of the NdFeB magnet are improved, the intrinsic coercivity is increased by 1.72kOe, the oxygen content is reduced by 188ppm, and the Al content in the composition is increased by 0.07wt%. That is, only the difference between encapsulation and non-encapsulation during sintering has produced a relatively obvious performance difference. The technical solution of the present invention optimizes the performance of the magnet in an extremely simple way.
Claims
1. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets, characterized in that: The sintering preparation method comprises: orienting and molding the magnet into powder, then wrapping it with metal foil and vacuum shaping it, and then performing protective heat treatment to obtain the NdFeB magnet; The magnet powder has a particle size of 2 to 5 μm, and is obtained by melting, quick solidification, hydrogen cracking and powdering of the primary magnet R-Fe-BM; R is at least one of Nd, Pr, Tb, Dy, Gd, La, Ho and Ce, and M is at least one of Al, Ga, Cu, Zr and Co; the metal foil includes Al and / or Sn, and the content is 99 to 99.9%; Vacuum shaping includes putting the magnet powder wrapped by metal foil into a vacuum bag, and then evacuating, isostatically pressing and removing the vacuum bag to balance the pressure. The isostatic pressing is to press at 220 MPa to obtain a density of 4.65 g / cm 3 intermediates; Protective heat treatment includes sintering, tempering and aging treatment; the sintering temperature is 1030-1100 °C, and the duration is 1-10 h; the tempering temperature is 850-950 °C, and the duration is 1-10 h; the aging temperature is 450-650 °C, and the duration is 1-10 h.
2. The sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The mass content of R in the primary magnet is 26-35 wt%, the mass content of B is 0.8-1.2 wt%, the mass content of M is 0.1-5.0 wt%, and the balance is Fe.
3. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The R is Nd and Dy; The M is Al, Ga, Cu, Zr and Co.
4. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The R is Nd, Pr and Dy; The M is Al, Ga, Cu, Zr and Co.
5. The sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The thickness of the metal foil is 0.001-0.200 mm.
6. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The thickness of the metal foil is 0.001-0.02 mm.
7. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The magnet powder is placed in a magnetic field of 15 kOe for orientation molding to obtain a green body.
8. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 7, characterized in that: Green density is 3.95 g / cm 3 .
9. A sintering preparation method for improving the intrinsic coercivity of NdFeB magnets according to claim 1, characterized in that: The protective heat treatment is performed in vacuum or protective atmosphere.
Citation Information
Patent Citations
Antioxidant used for preparing sintered NdFeB (neodymium iron boron) permanent magnet material
CN103184051A
Preparation method of anti-oxidation neodymium-iron-boron magnet
CN108511180A
High-performance low-cost rear earth permanent magnet material and preparation method thereof
CN104575906A
Preparation method of sintering neodymium iron boron sheet magnet
CN106783131A
Ferromagnetic material with giant negative magnetoresistance effect and preparation method thereof
CN110459377A